The first sentence of ontology: the justifying and justified Parmenides - Bańka, Jakub Sebastian (Folia Philosophica, 2003)
The author of the present article has attempted to point to the focal point around which both the Greeks’ ontological research, and the fundamental problem of European philosophy. Therefore, he has taken into consideration the first sentence from his poem Peri Physeos: “Being and thinking are the same”. According to the author of the article, the above formula expresses the fundamental relation between being and thought which are thus ascribed to each other. Essential here is the fact that this formula - although it is not justified in itself - justifies not only all of Parmenides’s statements, but also provides a foundation for the whole of Greek philosophy, and the whole of the later philosophical reflection.